THE INFLUENCE OF PEER TO PEER LENDING (P2P) AND ELECTRONIC MONEY ON INCREASING PROFITS OF MICRO SMALL AND MEDIUM ENTERPRISES (MSME) IN KUDUS REGENCY - Rhealin Hening Karatri; Keke Tamara Fahira; Rozaq Muhammad Yasin (Journal of Management and Islamic Finance, 2022)
Currently, MSMEs must begin to realize the importance of various digital platform services such as peer to peer lending (P2P) and electronic money. The low number of MSME business actors in Kudus Regency compared to MSME business actors in other regencies is one of the reasons for conducting this research. In addition, there is still a lack of research on Peer to peer lending (P2P) and electronic money with the use of connecting/intervening variables. The sampling technique used purposive sampling. The data was obtained using a questionnaire distributed to 91 MSME business actors in Kudus Regency.  Consumer data were analyzed using multiple regression models and path analysis with SPSS.  The results show that there is a direct influence of P2P and electronic money on the increase in MSME profits, the indirect influence of P2P and electronic money on the increase in MSME profits with MSME income as intervening, as well as the direct influence of P2P and electronic money on MSME income.